Is This a "Fettecke" or Just a "Greasy Corner"? About the Capability of Laypersons to Differentiate between Art and Non-Art via Object's Originality. (December 2014) - Haertel, Manuela; Carbon, Claus-Christian
Which components are needed to identify an object as an artwork, particularly if it is contemporary art? A variety of factors determining aesthetic judgements have been identified, among them stimulus-related properties such as symmetry, complexity and style, but also person-centred as well as context-dependent variables. We were particularly interested in finding out whether laypersons are at all able to distinguish between pieces of fine art endorsed by museums and works not displayed by galleries and museums. We were also interested in analysing the variables responsible for distinguishing between different levels of artistic quality. We ask untrained (Exp.1) as well as art-trained (Exp.2) people to rate a pool of images comprising contemporary art plus unaccredited objects with regard to preference, originality, ambiguity, understanding and artistic quality. Originality and ambiguity proved to be the best predictor for artistic quality. As the concept of originality is tightly linked with innovativeness, a property known to be appreciated only by further, and deep, elaboration (Carbon, 2011 i-Perception, 2, 708–719), it makes sense that modern artworks might be cognitively qualified as being of high artistic quality but are meanwhile affectively devaluated or even rejected by typical laypersons—at least at first glance.